Chronic Hepatitis B Virus Infection: The Relation between Hepatitis B Antigen Expression, Telomere Length, Senescence, Inflammation and Fibrosis. - Phaedra M Tachtatzis; Aileen Marshall; Aloysious Arvinthan; Suman Verma; Sue Penrhyn-Lowe; Marianna Mela; Cinzia Scarpini; Susan E Davies; Nicholas Coleman; Graeme J M Alexander (PLoS ONE)
Background Chronic Hepatitis B virus (HBV) infection can lead to the development of chronic hepatitis, cirrhosis and hepatocellular carcinoma. We hypothesized that HBV might accelerate hepatocyte ageing and investigated the effect of HBV on hepatocyte cell cycle state and biological age. We also investigated the relation between inflammation, fibrosis and cell cycle phase. Methods Liver samples from patients with chronic HBV (n = 91), normal liver (n = 55) and regenerating liver (n = 15) were studied. Immunohistochemistry for cell cycle phase markers and HBV antigens was used to determine host cell cycle phase. Hepatocyte-specific telomere length was evaluated by quantitative fluorescent in-situ hybridization (Q-FISH) in conjunction with hepatocyte nuclear area and HBV antigen expression. The effects of induced cell cycle arrest and induced cellular senescence on HBV production were assessed in vitro. Results 13.7% hepatocytes in chronic HBV had entered cell cycle, but expression of markers for S, G2 and M phase was low compared with regenerating liver. Hepatocyte p21 expression was increased (10.9%) in chronic HBV and correlated with liver fibrosis. Mean telomere length was reduced in chronic HBV compared to normal. However, within HBV-affected livers, hepatocytes expressing HBV antigens had longer telomeres. Telomere length declined and hepatocyte nuclear size increased as HBV core antigen (HBcAg) expression shifted from the nucleus to cytoplasm. Nuclear co-expression of HBcAg and p21 was not observed. Cell cycle arrest induced in vitro was associated with increased HBV production, in contrast to in vitro induction of cellular senescence, which had no effect. Conclusion Chronic HBV infection was associated with hepatocyte G1 cell cycle arrest and accelerated hepatocyte ageing, implying that HBV induced cellular senescence. However, HBV replication was confined to biologically younger hepatocytes. Changes in the cellular location of HBcAg may be related to the onset of cellular senescence.